Determinants for table tennis performance in elite Scottish youth players using a multidimensional approach: A pilot study - Picton Doherty, S. A.; Martinent, G.; Martindale, A.; Faber, I. R. (High Ability Studies, 2018)
The purpose of the study is to explore whether a multidimensional profiling approach can be useful in predicting a table tennis player`s actual and future (one year later) performance. Data on anthropometrics, age from peak height velocity, motor-skills, psychological skills and training histories were gathered among Scottish elite youth male table tennis players (n = 14). Significant correlations emerged between: (a) actual performance rating and age from peak height velocity (r = .71), sprint test (r = -.69), number of years of practice (r = .84), positive refocusing (r = -.58), and self-regulation in learning - self-monitoring (r = -.60), and evaluation (r = .57); (b) performance rating one year later and positive refocusing (r = -.58), self-monitoring (r = -.50), and number of years of practice (r = .80). Results also showed significant correlations between progression scores (2017 rating score minus 2016 rating score) and age from peak height velocity (r = -0.77), sprint test (r = .63), number of years of practice (r = -.52), self-monitoring (r = .69), and evaluation (r = -.58). These results provided preliminary evidence for the usefulness of a multidimensional profiling approach for predicting performance and progression in youth table tennis players.